2012
DOI: 10.12693/aphyspola.121.205
|View full text |Cite
|
Sign up to set email alerts
|

Internal Barrier Layer Capacitance Effects in Neodymium Copper Tantalate Ceramics

Abstract: A new perovskite material Nd 2/3 CuTa 4 O 12 was applied as a naturally formed internal barrier layer capacitor. The powder prepared by solid state synthesis and ball milling was pressed into pellets and sintered at 1180-1220• C. Dielectric properties of ceramic samples were characterized by impedance spectroscopic studies carried out in the temperature range from −55 to 700• C at frequencies 10 Hz ÷ 2 MHz. Two types of the dielectric response were revealed -a high frequency response attributed to grains which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The heterogeneous electrical microstructure and the relevant IBLC effect have been observed in various Cu‐containing materials, among which CaCu 3 Ti 4 O 12 (CCTO) ceramic is the well‐known material containing semiconducting grains and insulating grain boundary . Two models based on the cation (Cu) or anion (O) compositional difference between the grains and grain‐boundary regions have been proposed to account for the heterogeneous electrical microstructure in CCTO ceramics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterogeneous electrical microstructure and the relevant IBLC effect have been observed in various Cu‐containing materials, among which CaCu 3 Ti 4 O 12 (CCTO) ceramic is the well‐known material containing semiconducting grains and insulating grain boundary . Two models based on the cation (Cu) or anion (O) compositional difference between the grains and grain‐boundary regions have been proposed to account for the heterogeneous electrical microstructure in CCTO ceramics.…”
Section: Resultsmentioning
confidence: 99%
“…In the Cu compositional difference model, the grains in CCTO contain semiconducting Cu‐deficient phase and the Cu ion segregation along the grain‐boundary regions leads to a thin, insulating Cu‐rich phase . For the O compositional difference model, oxygen loss occurs during the sintering procedure forming semiconducting grains, and limited reoxidization took place along the grain‐boundary regions during the cooling procedure to form a thin, insulating grain boundary …”
Section: Resultsmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) studies revealed dense microstructure with grains 1-5 m in diameter. The energy-dispersive X-ray spectroscopy (EDS) microanalysis showed that grain boundaries are enriched with oxygen and tantalum, while grain interiors in copper (Szwagierczak and Kulawik, 2010, Szwagierczak, 2012. Such phenomena as evaporation of copper oxide, partial reduction of Cu 2ϩ to Cu ϩ ions (above 1,030°C in air) and small oxygen loss are known to occur during the sintering process.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous publications have been devoted to the structure, properties and applications of CaCu 3 Ti 4 O 12 single crystals, ceramics and thin films (Subramanian et al , 2000; Sinclair et al , 2002; Ramirez et al , 2009; Schmidt et al 2012; Thongbai et al , 2013). Other members of this family, like Bi 2/3 Cu 3 Ti 4 O 12 (Szwagierczak, 2009; Tan et al , 2010), Cu 2 Ta 4 O 12 (Ebbinghaus, 2007; Szwagierczak and Kulawik, 2008), Dy 2/3 CuTa 4 O 12 (Szwagierczak and Kulawik, 2010), Nd 2/3 CuTa 4 O 12 (Szwagierczak, 2012) and Bi 2/3 CuTa 4 O 12 (Szwagierczak and Kulawik, 2013), were not so intensively studied. Furthermore, only a few publications have reported on the application of these high permittivity materials in multilayer ceramic capacitors (Barbier et al , 2009; Szwagierczak and Kulawik, 2013; Kulawik et al , 2013; Löhnert et al , 2015), the most widely used passive electronic components.…”
Section: Introductionmentioning
confidence: 99%